FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP LANSIA - Chaniago, Yona Rameyza Elya; Asmaracha Nindiatma, Bintang (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2025)
The quality of life of the elderly 60-74 years usually experiences a lot of decline both physically, psychologically, and socially. As the quality of life of an elderly person decreases, diseases that attack an elderly person will appear. Quality of life is important in the life of the elderly, namely increasing the life expectancy of the elderly. The purpose of this study is for readers to understand several factors that can affect the quality of life of the elderly. This research uses literature review from several articles. Data was obtained using the Publish or Perish application from Google Schoolar and there were 200 articles, after reviewing 5 suitable articles. Based on the analysis of the literature review, there are several factors that affect the quality of life of the elderly ranging from nutritional status, independence, mindfulness, psychosocial, and obesity. Nutritional status which can be seen from the elderly's food consumption, independence which causes the elderly not to depend on others, mindfullnes fosters good psychological function, psychosocial which means a decrease in reciprocal relationships that cause the elderly to feel lonely, and obsessiveness caused by excessive diet.